Voice pitch is negatively associated with sociosexual behavior in males but not in females - Alvaro Mailhos; Damián-Amaro Egea-Caparrós; Álvaro Cabana; Francisco Martínez-Sánchez (Frontiers in Psychology, 2023)
Acoustic cues play a major role in social interactions in many animal species. In addition to the semantic contents of human speech, voice attributes – e.g., voice pitch, formant position, formant dispersion, etc. – have been proposed to provide critical information for the assessment of potential rivals and mates. However, prior studies exploring the association of acoustic attributes with reproductive success, or some of its proxies, have produced mixed results. Here, we investigate whether the mean fundamental frequency (F0), formant position (Pf), and formant dispersion (Df) – dimorphic attributes of the human voice – are related to sociosexuality, as measured by the Revised Sociosexual Orientation Inventory (SOI-R) – a trait also known to exhibit sex differences – in a sample of native Spanish-speaking students (101 males, 147 females). Analyses showed a significant negative correlation between F0 and sociosexual behavior, and between Pf and sociosexual desire in males but not in females. These correlations remained significant after correcting for false discovery rate (FDR) and controlling for age, a potential confounding variable. Our results are consistent with a role of F0 and Pf serving as cues in the mating domain in males but not in females. Alternatively, the association of voice attributes and sociosexual orientation might stem from the parallel effect of male sex hormones both on the male brain and the anatomical structures involved in voice production.